2020
DOI: 10.1186/s12865-020-00358-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of berberine in non-alcoholic fatty liver disease via the Angptl2 pathway

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) has become the most common liver disease worldwide. Recent studies have shown that the Angptl2 pathway mediated hepatic inflammatory response plays an important role in the progression of nonalcoholic fatty liver disease. Our study investigated the possible molecular mechanisms of berberine (BBR) in the treatment of the liver inflammatory response in the livers of rats with high-fat diet-induced NAFLD via the Angptl2 pathway. Results: At the end of 12 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…In the present study, the incidence of T2DM was significantly lower in the berberine group than in the IGT group, and 40% of rats in the berberine group reverted to having an NGT. Moreover, treatment with berberine led to significant improvements in blood glucose level, blood lipid levels, and insulin resistance, as supported by the literature (42)(43)(44)(45)(46)(47)(48). To our knowledge, this is the first study to demonstrate that berberine can prevent the progression of prediabetes to T2DM in rats.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…In the present study, the incidence of T2DM was significantly lower in the berberine group than in the IGT group, and 40% of rats in the berberine group reverted to having an NGT. Moreover, treatment with berberine led to significant improvements in blood glucose level, blood lipid levels, and insulin resistance, as supported by the literature (42)(43)(44)(45)(46)(47)(48). To our knowledge, this is the first study to demonstrate that berberine can prevent the progression of prediabetes to T2DM in rats.…”
Section: Discussionsupporting
confidence: 69%
“…Our previous study found that berberine decreased blood glucose level and insulin resistance in rats with T2DM induced by a highfat diet (31). Previous studies also reported that berberine could improve the blood markers and pathophysiological changes of diabetes in patients and animal models (42)(43)(44)(45)(46)(47)(48). In the present study, the incidence of T2DM was significantly lower in the berberine group than in the IGT group, and 40% of rats in the berberine group reverted to having an NGT.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations